SLANG WORD USED IN COMMENT OF TYLER’S YOUTUBE CHANNEL - Suparyana, Gede Adi Surya (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTThe title of this paper is "Slang Word Used in Comment of Tyler’s YouTube Channel". Theresearch data was taken from the comment that contains slang words in Tyler’s YouTube Channel.Data collection was carried out through documentation methods by reading, selecting the commentand taking notes. Then classified based on theory. The descriptive qualitative method is used toanalyze the data that has been found. The collected data were analyzed qualitatively anddescriptively based on the slangs theory proposed by Allan and Burridge (2006) in his bookentitled Forbidden Words: Taboo and The Censoring of Language. From the results of the analysis,it is known that a lot of slangs variation used in the comment section of Tyler’s YouTube channel.The author used the theory proposed by Allan and Burridge (2006) to categorize types of slangthat are found in data or comment on Tyler’s YouTube channel. There are five types of slang thatare found in this research which are fresh and creative, flippant, imitative, acronym and clipping.The acronym type is the most frequent type used by people in the comment section of the TylerYouTube Channel.Keywords: Slang Word, Tyler, YouTube, Comment, Type of Slang.ABSTRAKJudul tulisan ini adalah "Kata Gaul yang Digunakan dalam Komentar Saluran YouTube Tyler".Data penelitian diambil dari komentar yang berisi kata-kata slang di channel YouTube Tyler.Pengumpulan data dilakukan melalui metode dokumentasi dengan membaca, memilih komentardan mencatat. Kemudian diklasifikasikan berdasarkan teori. Metode deskriptif kualitatifdigunakan untuk menganalisis data yang telah ditemukan. Data yang terkumpul dianalisis secarakualitatif dan deskriptif berdasarkan teori slang yang dikemukakan oleh Allan dan Burridge(2006) dalam bukunya yang berjudul Forbidden Words: Taboo and The Censoring of Language.Dari hasil analisis diketahui bahwa banyak sekali variasi slang yang digunakan di kolomkomentar channel YouTube Tyler. Penulis menggunakan teori yang diajukan oleh Allan danBurridge (2006) untuk mengkategorikan jenis slang yang ditemukan dalam data atau komentar disaluran YouTube Tyler. Ada lima jenis slang yang ditemukan dalam penelitian ini yaitu fresh andcreative, flippant, imitative, akronim dan clipping. Akronim adalah jenis slang yang paling seringdigunakan oleh orang-orang di kolom komentar YouTube Tyler.Kata Kunci: Kata – kata gaul, Tyler, YouTube, Komentar, Tipe – tipe slang.